Restoring Inanna - an ancient myth for contemporary women? - Bruinsma, Raelene (Curtin University, 2014)
Combining a range of performative methods, including original song and platform storytelling, this autoethnographic practice-led feminist study explores the ways in which the 4-5000 year stories and poems of the goddess Inanna from Ancient Sumer (present day Iraq) speak to contemporary women. Weaving together data gained from creative practice, trial performances, contextual research and discussion forums, the results are presented in a live one woman performance, documented in an accompanying DVD, and a written exegesis.